ADDITIONAL OF CHEMICAL ENHANCER FOR INCREASING THE PENETRATIONAL FLUORIDE MOUSE SKIN: PENAMBAHAN BAHAN KIMIA UNTUK PENINGKATAN DAYA TEMBUS ION FLUORIDA PADA KULIT TIKUS - Diyah Fatmasari; Iwan Dwi Prahasto; Akhmad Kharis Nugroho; Widjijono (Dentika: Dental Journal, 2012)
Fluoride plays an important roles in reducing dental caries by improving remineralization process and strengthening email through forming fluoroapatite which is more resistant to acid. Fluoride systemic mode without passing metabolism with small and controlled dose need to be developed such as Transdermal route. The aims of this research was to find if fluoride solution with and without enhancer solution is able to penetrate to skin. Quasy experimental design with post test only control group design as research approach was used. Transport test with Franz Like Diffusion cell used as the instrument in vitro skin permeation test with hairless and full thickness mouse skin as membrane between donor and recipient cell. Two groups of donor cell was fluoride solution and fluoride added with chemical enhancer: oleic acid and iso propyl alcohol (IPA) solution and recipient solution was CMF PBS 0,1 M pH 7,4. Control group was oleic acid solution. Sample was taken for time interval of 4, 20 and 24 hours and Fluoride containt was measured by Potensiometer Spesific Ion Fluoride. The results showed that there was an influence of transport test both on NaF solution and NaF+oleat acid and IPA solution (p= 0.00) and (0.00) on fluoride permeation, however there was no significant difference on control group (p= 0.07). NaF added with chemical enhancer solution and it had higher penetrating power than other solution. It can be concluded that added chemical enhancer can increase the penetration of fluoride.